Antropologia ekologiczna w hiszpańskim dyskursie tauromachicznym - Ziółkowska-Kuflińska, Magdalena (Studia Etnologiczne i Antropologiczne, 2017)
Tradition of bullfight (corrida de toros) in Spanish society is subject to changes and modifications. More orthodox opponents in their views postulate, for example, switching to vegetarianism, as a direct implication would be justified by the need to move away from mass production of meat. Opponents accuse the farmers that “a good life” before death is what a bull deserves as a reward for his part in the fight. The most important issue is the size of the pasture, where most of the year the animals can move freely. If we reflect on the meaning of the existence of these species or races, we will realize that it is entirely correlated to human needs. It should be, however, considered whether people have a moral right to form species and breeds just to satisfy our cravings.